Between Dietary Patterns and Glycemic Control in Type 2 Diabetes Patients at Margajaya Community Health Center, Bekasi - Safitri, Indah Lia; Woro, Meria; Thomasita Batubara , Salamah (Nursing Genius Journal, 2025)
Background: The prevalence of diabetes in Indonesia has increased rapidly from 6.9% of cases in 2013 to 8.5% of cases in 2018. In fact, according to WHO, the estimate of people with diabetes in Indonesia will increase rapidly to 21.3% in 2030. One of the risk factors for increased blood sugar levels is poor diet. Objective: To determine the relationship between dietary patterns and blood glucose levels in patients with type 2 diabetes mellitus in the Margajaya Health Center Area, Bekasi City. Method: This study is a quantitative study with a cross- sectional approach. The sample in this study were all patients with type 2 diabetes mellitus who routinely undergo treatment at the Margajaya Health Center in Bekasi City, totaling 60 respondents. The sampling technique used total sampling. The instruments used were questionnaires and blood sugar testing tools. Results: Research using the chi-square test was calculated using SPSS version 26, the results obtained were a P Value of 0.021<0.05. Conclusion: There is a relationship between the patterns eating on blood sugar levels in type 2 DM sufferers